2014
DOI: 10.11648/j.jps.20140205.16
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Pharmacological Active Compounds of the Asteraceae Family and their Chemotaxonomical Implications

Abstract: It can be assumed that sesquiterpene lactones and natural phytosteroids (ecdysones) are the characteristic compounds of the plants from the Asteraceae family. They display certain pharmacological properties and thus are helpful in chemical descriptions of the Asteraceae tribes, subtribes and species. Also some phenolic glycosides found in genus Klasea Cass, and in genus Centaurea L. may be of medical and chemotaxonomical significance. Our studies on the species of the aforementioned taxons and the isolation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…41 For instance, sesquiterpene lactones (SL) identified in the Asteraceae family have exhibited anti-microbial and antiinflammatory properties, among others. 42 Furthermore, plants usually possess a wide collection of freeradical-scavenging molecules, highlighting the potential of PC as well as other molecules such as nitrogen compounds, vitamins, or terpenoids (Te). 43 Several species from the Asteraceae family are known for their Te (SL) and PC (flavonoids (F) and phenolic acids (PA)) contents-both responsible for their antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%
“…41 For instance, sesquiterpene lactones (SL) identified in the Asteraceae family have exhibited anti-microbial and antiinflammatory properties, among others. 42 Furthermore, plants usually possess a wide collection of freeradical-scavenging molecules, highlighting the potential of PC as well as other molecules such as nitrogen compounds, vitamins, or terpenoids (Te). 43 Several species from the Asteraceae family are known for their Te (SL) and PC (flavonoids (F) and phenolic acids (PA)) contents-both responsible for their antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that some phenolic compounds might also be responsible for the antimigraine effect of T. parthenium . These compounds reduce lactate dehydrogenase (LDH) release, nitrite levels and 5-HT, and thus, they cause antioxidant and antiapoptotic effects [12].…”
Section: Introductionmentioning
confidence: 99%